Early career trajectories of first- and second-generation migrant graduates of professional university. Issue 10 (27th July 2022) - Belfi, Barbara; Allen, Jim; Jacobs, Babs; Levels, Mark; van Oosterhout, Kars
ABSTRACT: This study explores how the careers of professional university graduates with a first- or second-generation non-Western migrant background evolve within the first four to eight years after graduation, as compared to their Dutch native peers. We find that in the first year after graduation, while holding constant background characteristics, both first- and second-generation migrants experienced lower employment chances, more skill mismatches and lower job satisfaction than natives. No wage differences could be observed between migrants and natives. Although the differences between first- and second-generation migrants appeared to be small in the short term, a follow-up survey four to eight years after graduation revealed evidence that second-generation – but not first-generation – migrants improved their situation overall. They maintained earnings parity with natives, and narrowed the gap in terms of job satisfaction, skill match, and to a somewhat lesser extent employment chances. Although the first generation eliminated the gap with respect to natives in terms of employment chances, they continued to show lower job satisfaction and opened up a wage gap as compared to their native Dutch peers. This suggests that early-career gaps for first-generation migrants are enduring and cannot easily be resolved.